Professor educational beliefs: take a learner-centered teaching approach? - Edurne Chocarro de Luis; Ángel Sobrino Morrás; Mª del Carmen González-Torres (Universidad de La Rioja, 2014)
This article presents the results obtained from a process based on questionnaires and interviews to lectures, with the aim of learn about their educational beliefs. The interest of this research is the important role that these beliefs play in the usual teaching decisions that professors make. The European Higher Education Area requires new teaching strategies which are summarized in an education model that is focused in the student and his learning. This approach will be more easily implemented if all professors share its principles. The present study concludes that professors do share that principles but certain ideas are still present which make difficult to put the principles entirely in practice.